Análise ambiental do ICMS verde nas políticas públicas para preserva - ção da Amazônia: estudo de caso em municípios do Baixo Amazonas - GIORDANO, Caroline Leite (Universidade Federal do Oeste do Pará, 2023)
The present work proposes to answer the research problem related to the environmental public policy of Green value added tax in the state of Pará, implemented by State Law nº. 7,638/2012, previously regulated by State Decree no. 1,696/2017 and currently by State Decree no. 1,064/2020, in order to ascertain the respective contribution to the creation and maintenance of protected areas and reduction of deforestation, using the Lower Amazon region, created by State Decree nº. 1,066/2008, located in the west of Pará, as well as performing an analysis of the inducing and compensatory economic instrument, presenting the concept, purpose, legal nature of non-binding, index calculation methodology for transfer purposes, in the period from 2014 to 2019, in perspective of payments for environmental services. Another objective of the dissertation is to fill in the gaps that are not cataloged in official bodies, such as data regarding municipal legislation regarding ICMS Verde and protected areas, obtained through letters sent in the preparatory administrative procedure PP no. 004217-031/2015 that is being processed before the Agricultural Prosecutor's Office of Santarém or provided by the servers of the prefectures or municipal councils, through email, call or message via Whatsapp, when such information is absent in the procedure, considering the context of the COVID pandemic -19. In this sense, the case study method was used, considering that the Green value added tax experience lived in the specific case of the Lower Amazon region was prioritized, in order to identify the similarities and differences between the municipalities belonging to the region and the contribution to reduction of deforestation and preservation of protected areas. Finally, it is inferred that the instrument studied was not able to improve deforestation rates in the municipalities of the Lower Amazon region, on the other hand, it contributed to the maintenance of existing protected areas and the creation of new ones, in addition to having contributed to the entities in the region studied to organize and create their respective municipal environmental systems, contributing to the implementation not only of Green value added tax, but also of other local environmental public policies, such as the green bag.